Self-confidence as a Supporting Factor for Public Speaking Skills of Prospective Guidance Teachers - Khairiah Sari, Azmatul; Sari, Rahmahidayati; Rahma Nengsi, Ayu; Intan Wahyuni, Sri (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
This paper documents the assessment of self-confidence related to student public speaking skills among BK UNP students because good public speaking is supported by good self-confidence. The research was carried out using a mixed method through the research instruments of questionnaires supported by interviews and observations from 50 students taken at random. The questionnaire has been validated with content and empirical validities and produced a validity index of 0.85 and a reliability index of 0.90. This research result reveals that BK UNP students have good self-confidence when they apply public speaking. Based on the interview and observation results conducted on students, it was found that students should have preparation for appearing in public, either in terms of preparing the material they want to convey and their needs when appearing and overcoming anxiety or before appearing and knowing some common words used by listeners. Due to the limitations of researchers, we only discuss one factor that supports female students' public speaking, self-confidence. It is recommended that future researchers conduct research related to public speaking skills in more depth and breadth by looking at other factors that influence public speaking skills and the methods used to improve public speaking skills.